PERANCANGAN SISTEM INFORMASI WEBSITE SEPATU HANDMADE PADA TOKO PRICHILLASHOES: Handmade Shoes, Information System, Web Of Sale. - Susanto, Darex; Rahayu, Prima (JURNAL AKADEMIKA, 2023)
Web-based handmade shoe sales are made to make it easier for people to find information about the latest handmade shoe products and those who want to have shoes with unique designs. This study uses research methods such as observation, interviews, literature study. As for the system development method using the System Development Lyfe Cycle (SDLC). Based on the results of the research, the design of this information system can make it easier for buyers to introduce information about the latest handmade shoe products and make it easier to process sales transaction data and be able to overcome problems if an error occurs in ordering a product.